Ensuring equal parental responsibility: a study on the retrospective application of Section 32 of the Children Act 2022 in Kenya in line with the child’s best interests standard - Mbuvi, D. N. (Strathmore University, 2024)
The enactment of the Children Act No. 29 of 2022 marked a significant legal shift, replacing the outdated Children Act of 2001. The primary objective of the new Act is to align with Article 53 of the Constitution, which provides for the paramount consideration of a child's best interests in all matters concerning children. In line with the best interests of the child, the Children Act 2022 introduces the concept of equal parental responsibility regardless of whether children were born in wedlock or not. This amended the provisions of the Children Act 2001 where fathers had to undergo specific legal processes to acquire parental rights. The primary concern explored in this research is the potential retrospective application of Section 32 of the Children Act 2022 to past cases involving fathers who, under the 2001 Act, were considered 'unqualified fathers.' Unqualified fathers in this context means fathers who were not granted parental responsibility in the first instance under the 2001 Children Act. The research engages the doctrine of necessary implication, a rule of statutory construction, to analyse whether the Act can be interpreted as having retrospective effects. While the Act lacks an express provision on retrospective application, the study contends that the doctrine of necessary implication suggests a retroactive intent by the legislators. The research primarily bases its arguments on the child’s best interest standard. The paper argues that this retrospective application will contribute to the well-being of children by ensuring equal parental responsibility in the first instance. The overarching goal is to align Section 32 of the Children Act with the constitutional mandate under Article 53 to safeguard the best interests of the child. By scrutinizing the Children Act 2022 and advocating for its retrospective interpretation, the study aims to provide valuable insights and recommendations for the legal community, policymakers, and stakeholders involved in child welfare and family law.
Full - text undergraduate research project